2003
DOI: 10.1002/jnr.10677
|View full text |Cite
|
Sign up to set email alerts
|

Hyperalgesic effects of γ‐aminobutyric acid transporter I in mice

Abstract: The present study focused on the involvement of gamma-aminobutyric acid transporter I (GAT1) in pain. We found that GABA uptake was increased in mouse spinal cord at 20 min and 120 min after formalin injection and in mouse brain at 120 min, but not 20 min, after formalin injection. In addition, the antinociceptive effects of GAT1-selective inhibitors were examined using assays of thermal (tail-flick) and chemical (formalin and acetic acid) nociception in C57BL/6J mice. The GAT1-selective inhibitors, ethyl nipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…The hot plate test assesses supraspinal mediated pain processing that involves somatosensory cortex and GABAergic transmission. Transgenic mice lacking GAD-65 demonstrated hyperalgesia, while mice bred to overexpress the GABA transporter GAT-1, altering the tonic GABA levels in the synaptic environment, exhibited hyperalgesia to a variety of thermal and chemical nociceptive challenges (Hu et al, 2003). In our study, mice exposed to CO in utero had significantly shorter hot plate latencies compared to controls, consistent with previous reports that alterations in GABAergic activity can influence nociception.…”
Section: Co Administration During Neocortical Development Leads To Alsupporting
confidence: 91%
“…The hot plate test assesses supraspinal mediated pain processing that involves somatosensory cortex and GABAergic transmission. Transgenic mice lacking GAD-65 demonstrated hyperalgesia, while mice bred to overexpress the GABA transporter GAT-1, altering the tonic GABA levels in the synaptic environment, exhibited hyperalgesia to a variety of thermal and chemical nociceptive challenges (Hu et al, 2003). In our study, mice exposed to CO in utero had significantly shorter hot plate latencies compared to controls, consistent with previous reports that alterations in GABAergic activity can influence nociception.…”
Section: Co Administration During Neocortical Development Leads To Alsupporting
confidence: 91%
“…Another level of regulation of GABA signaling occurs with the GABA reuptake transporters (GATs), of which four have been identified (GAT1-4). Studies of mice that overexpress GAT1 demonstrated increased pain-like behavior, and conversely, GAT1 knockout mice showed decreased pain-like behaviors to mechanical and thermal stimulation (Hu et al, 2003;Xu et al, 2008). Additionally, GAT1 knockout mice exhibit lower basal levels of anxiety-like and depressive-like behaviors as well as a lower basal plasma CORT (Liu et al, 2007), findings that were replicated with chronic dosing of the GAT1 inhibitor tiagabine (Thoeringer et al, 2010).…”
Section: Novel Targets For Stress-induced Painsupporting
confidence: 64%
“…It is generally accepted that pain sensation can be suppressed by acupuncture, and it has been demonstrated that acupuncture in its analgesic effect interferes with the glutamatergic system [1] . Experiments with transgenic mice with knock-out or over expressed GABA transporter have demonstrated that the GABA transporter is involved in pain sensation [2] . Therefore, the authors may speculate that modulation in the activity of the transporters for glutamate and GABA as well as the sodium pump may be involved in the mechanism of pain suppression by acupuncture.…”
mentioning
confidence: 99%